Reforming Digitalizing the Legal System in Indonesia to Confront National and Global Challenges - Atabiya, Muhammad Haikal; Purwanto, Ade Candra Kurnia (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: Indonesia, as a state based on law (rechtsstaat), faces increasingly complex challenges in the 21st century, both nationally and globally. Issues such as corruption, regulatory disharmony, weak human rights protection, transnational crime, climate change, global trade, and the rise of digital technology demand a fundamental transformation of the legal system.Purposes of the Research: This study aims to analyze the urgency of reforming and digitalizing Indonesia’s legal system to address national issues while simultaneously harmonizing with international legal standards. The research seeks to identify strategic steps that strengthen law enforcement, simplify regulations, and integrate digital technology into the legal process.Methods of the Research: The research applies a normative legal research method as explained by Peter Mahmud Marzuki, combining three approaches: the statute approach, to examine the 1945 Constitution and other regulations; the conceptual approach, to analyze fundamental legal concepts such as the rule of law and harmonization; and the comparative approach, to assess Indonesian legal practices in comparison with other countries, especially in the fields of digital law, human rights, and international cooperation.Results Main Findings of the Research: The findings indicate that the transformation of Indonesia’s legal system is necessary in four key aspects: (1) regulatory reform to reduce disharmony and overlaps, (2) strengthening law enforcement and eradicating corruption, (3) harmonization of national law with international legal frameworks, and (4) legal digitalization through e-court systems, blockchain, and artificial intelligence. These measures will enhance legal certainty, protect human rights, foster economic development, and improve Indonesia’s role in international diplomacy.